(untitled) (Journal of Bangladesh Academy of Sciences, 2023)
The stereochemistry of the routes to two different bicyclic tetramates are reported which enables to synthesize highly functionalized systems. An analysis of the structure shows that the tetramates permit ready incorporation of three to five functionality at different positions. This work demonstrates that novel bicyclic tetramates can be synthesized via stereoselective cyclization. The resulting heterocycles were studied with the help of NMR techniques. J. Bangladesh Acad. Sci. 47(2); 215-222: December 2023